2024
DOI: 10.1108/jaoc-01-2024-0028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of digital advancements on accounting, auditing and reporting literature: insights, practice implications and future research directions

Mustafa Raza Rabbani

Abstract: Purpose The study aims to use bibliometric and scientometric analysis to conduct a detailed investigation on the impact of disruptive technologies in accounting and reporting literature. To draw both academics and practitioners through accelerated research activities, the study also aims to look into the significance of these disruptive technologies, their potential and the opportunities they present for the accounting profession. Design/methodology/approach With the use of the Scopus database and a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…[31] indicates that higher R&D intensity and intellectual property are positively associated with firm survival and performance. Similarly, other studies have shown that intellectual property rights, like patents and trademarks, are also positively related to firm survival [32]. The authors analyzed the survival of British companies for 5 years and found that innovativeness is positively associated with the company's survival.…”
Section: Innovationmentioning
confidence: 83%
“…[31] indicates that higher R&D intensity and intellectual property are positively associated with firm survival and performance. Similarly, other studies have shown that intellectual property rights, like patents and trademarks, are also positively related to firm survival [32]. The authors analyzed the survival of British companies for 5 years and found that innovativeness is positively associated with the company's survival.…”
Section: Innovationmentioning
confidence: 83%